IMPLEMENTASI MBKM KEWIRAUSAHAAN : KUALITAS PRODUK HASIL PROSES OTOMATISASI BORDIR DI KONVEKSI INDAH COLLECTION - Boby Nurseptian Mulyawanto; Koerniawan Hidayat (Jurnal Abdi Insani, 2023)
The world of fashion has recently developed rapidly with increasingly advanced technology. Automatic computer embroidery is becoming more popular due to its high degree of accuracy and faster speed than conventional embroidery. Indah Collection is an embroidery convection located in North Jakarta which is strategic because it is close to many companies and MSMEs in North Jakarta which have great potential in terms of fashion. This activity aims to add insight and enthusiasm to partners in terms of using automatic machine embroidery, which previously used conventional embroidery. The method used is to use photo objects from several photo sources taken directly at Indah Collection. This method was taken because the resulting photo is a photo during the automatic embroidery process at the Indah Collection convection. In a world of technology that is now very sophisticated and also faster in doing various things. The result obtained in making the product is the quality of the product itself. With good product quality, prospective buyers will be satisfied and will make repeat purchases. It can be concluded that automatic embroidery convection and automation technology can provide benefits and conveniences for the community, especially MSMEs in meeting fashion needs and increasing task efficiency, but still require the role of humans as an important resource in the process. The suggestion for the future is that Convection Indah Collection can make even more designs, so that many consumers will come. The Indah Collection embroidery convection machine is relatively new, but occasionally performs periodic maintenance so that the Indah Collection automatic embroidery machine can run properly and maintains durability so that the quality of the embroidery machine production will be maintained.